Effectiveness Malaysian archival institutions now and future / Nurul Aida Jamil, Nur Atiqa Saleh and Fatin Eleena Sha'mar - Jamil, Nurul Aida; Saleh, Nur Atiqa; Sha'mar, Fatin Eleena (Faculty of Information Management, 2015)
This article examined the effectiveness of Archives Malaysian Archival Institutions management now and future. Archive is an institution responsible for appraisal, acquisition and provision of access to archival documents and made available for consultation. In a country there should have an archive to keep, preserve and conserve their historical materials and important document as evidence and reference for the future. In order to achieve "Wawasan 2020" and maintain the effectiveness on managing Archives the National Archive of Malaysia should overcome several challenges and make solutions to solving the challenges. This paper therefore addressed these following areas: the problems that have been faced archivist, strategies for effective Archive Management in Malaysian Archival Institutions and several recommendations or solution to solve the problems.